Environmental Pollution and Health Problems of Workers in Tobacco Industries (Journal of Life and Earth Science, 2011)
The effect of environmental pollution on subjective and mental health of the workers in tobacco industries has been investigated. A total of 540 workers, 340 from tobacco (polluted) industries and the remaining 200 from non-tobacco industries, were selected using simple random sampling technique. Workers included in the sample were interviewed with three measuring instruments: (a) The Inventory of Subjective Health, (b) The General Health Questionnaire and (c) The Interview Schedule on Personal and Health Related Questionnaire. The results showed that the workers of tobacco industries suffered more from subjective health and mental health related problems than those of the non-tobacco industries. The older (≥20 yrs) workers perceived relatively better subjective health than the younger (